International Society for Advancement of Cytometry (ISAC) flow cytometry shared resource laboratory (SRL) best practices. Issue 11 (3rd November 2016) - Barsky, Lora W.; Black, Michele; Cochran, Matthew; Daniel, Benjamin J.; Davies, Derek; DeLay, Monica; Gardner, Rui; Gregory, Michael; Kunkel, Desiree; Lannigan, Joanne; Marvin, James; Salomon, Robert; et al.
Abstract: The purpose of this document is to define minimal standards for a flow cytometry shared resource laboratory (SRL) and provide guidance for best practices in several important areas. This effort is driven by the desire of International Society for the Advancement of Cytometry (ISAC) members in SRLs to define and maintain standards of excellence in flow cytometry, and act as a repository for key elements of this information (e.g. example SOPs/training material, etc.). These best practices are not intended to define specifically how to implement these recommendations, but rather to establish minimal goals for an SRL to address in order to achieve excellence. It is hoped that once these best practices are established and implemented they will serve as a template from which similar practices can be defined for other types of SRLs. Identification of the need for best practices first occurred through discussions at the CYTO 2013 SRL Forum, with the most important areas for which best practices should be defined identified through several surveys and SRL track workshops as part of CYTO 2014. © 2016 International Society for Advancement of Cytometry